KEABSAHAN SURAT KUASA MUTLAK SEBAGAI DASAR PERALIHAN HAK ATAS TANAH - Muthia Hanna Qistina (2022)
The transfer of land rights is the transfer of land rights from the old holder to the new right holder legally based on the applicable laws and regulations. One way to transfer land rights is by buying and selling. In this process, it is known that there is an absolute power of attorney, the existence of this power is often misused which in the end causes losses to the party giving the power of attorney. The formulation of the problem in this study is regarding the validity of the use of absolute power of attorney as the basis for the transfer of land rights and the legal consequences of using absolute power of attorney as the basis for the transfer of land rights. This study used a normative juridical research method with a statutory approach and a case approach, and the data were analyzed using descriptive analysis. An absolute power of attorney is an agreement. The conditions for a valid agreement are agreement, competence, a certain thing, and a lawful cause. An absolute power of attorney contains elements of a prohibited cause, namely, contrary to the legislation. The use of absolute power in the transfer of land rights has an impact on the validity of the absolute power itself which in the absolute power contains clauses that are not lawful or forbidden. If the conditions for the validity of the agreement are not fulfilled, the agreement is invalid. The legal consequences arising from the use of absolute power in the transfer of land rights or the transfer of land rights are null and void.